2019
DOI: 10.1002/jmv.25649
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of DENV, JEV, and ZIKV among the indigenous people (Orang Asli) of Peninsular Malaysia

Abstract: Dengue virus (DENV), Japanese encephalitis virus (JEV), and Zika virus (ZIKV) are mosquito‐borne flavivirus of medical importance in tropical countries such as Malaysia. However, much remains unknown regarding their prevalence among the underserved indigenous people (Orang Asli) living in communities in the forest fringe areas of Peninsular Malaysia. Information on the prevalence of diseases is necessary to elevate the effectiveness of disease control and preventive measures. This study aimed to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…e present study observed a low prevalence of dengue (17%) among the forest fringe populations in comparison to those reported earlier. An even lower prevalence of dengue (4.9%) was reported more recently where the study also showed significantly higher presence of antibodies against Japanese encephalitis (48.4%) among the OA and some presence of IgG antibodies against Zika (13.2%) [17]. is serosurvey suggested that dengue prevalence had decreased over time among those living in forest fringe areas and that it is significantly different from that of the rural areas.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…e present study observed a low prevalence of dengue (17%) among the forest fringe populations in comparison to those reported earlier. An even lower prevalence of dengue (4.9%) was reported more recently where the study also showed significantly higher presence of antibodies against Japanese encephalitis (48.4%) among the OA and some presence of IgG antibodies against Zika (13.2%) [17]. is serosurvey suggested that dengue prevalence had decreased over time among those living in forest fringe areas and that it is significantly different from that of the rural areas.…”
Section: Discussionmentioning
confidence: 48%
“…Inclusion of climatic variables such as air temperature and rainfall should be considered in future studies, as is mosquito population and density. In addition, future studies should also address issues of dengue cross-reactivity with other arboviruses such as Zika and Japanese encephalitis in serological assays [17]. Since the study was performed approximately 10 years ago, it is possible that much societal and climate changes have occurred over the years, which could have affected the present dengue serological status among the OA.…”
Section: Journal Of Tropical Medicinementioning
confidence: 99%
“…The FRNT assay was implemented as previously described (Sam et al, 2019;Khor et al, 2020) with slight modification using mouse anti-ZIKV NS1 monoclonal antibodies (Abcam, UK) and HRP antibody (Abcam, UK) as secondary antibodies to stain foci formed by infected Vero cells (CCL-81). FRNT 90 was performed to validate the ELISA results and address potential bias to any commercially available ELISA kits.…”
Section: Foci Reduction Neutralization Testmentioning
confidence: 99%
“…Overweight and obesity were linked to hypertension among the indigenous community at Dourados, Mato Grosso do Sul of Central Brazil [34]. Notably, non-communicable diseases such as hypertension, diabetes mellitus, insulin resistance and cardiovascular diseases [11,33] are linked to overweight and obesity in addition to the infectious diseases, including soil-transmitted helminth, dengue, Japanese encephalitis, and Zika [35,36]. Nevertheless, studies on the relationship between overweight and obesity with hypertension and quality of life in Malaysia have been scarce.…”
Section: Literature Reviewmentioning
confidence: 99%